Cosmology with Binary Neutron Stars: Does Mass–Redshift Correlation Matter? - Soumendra Kishore Roy; Lieke A. C. van Son; Anarya Ray; Will M. Farr (The Astrophysical Journal Letters)
Next-generation gravitational-wave detectors are expected to detect millions of compact binary mergers across cosmological distances. The features of the mass distribution of these mergers, combined with gravitational-wave distance measurements, will enable precise cosmological inferences, even without the need for electromagnetic counterparts. However, achieving accurate results requires modeling the mass spectrum, particularly considering possible redshift evolution. Binary neutron star (BNS) mergers are thought to be less influenced by changes in metallicity compared to binary black holes or neutron star–black hole mergers. This stability in their mass spectrum over cosmic time reduces the chances of introducing biases in cosmological parameters caused by redshift evolution. In this study, we use the population synthesis code COMPAS to generate astrophysically motivated catalogs of BNS mergers and explore whether assuming a nonevolving BNS mass distribution with redshift could introduce biases in cosmological parameter inference. Our findings show that despite significant variations in the BNS mass distribution across binary physics assumptions and initial conditions in COMPAS , the joint mass–redshift population can be expressed as the product of the mass distribution marginalized over redshift and the redshift distribution marginalized over masses. This enables a 2% unbiased constraint on the Hubble constant—sufficient to address the Hubble tension. Additionally, we show that in the fiducial COMPAS setup, the bias from a nonevolving BNS mass model is less than 0.5% for the Hubble parameter measured at redshift 0.4. These results establish BNS mergers as strong candidates for spectral siren cosmology in the era of next-generation gravitational-wave detectors.